From Content Delivery to Knowledge Construction: Rethinking Digital Pedagogical Models - Handy Ferdiansyah; Aprinda Maharani; Benjamin Laurentino Vaz (The Indonesian Institute of Science and Technology Research, 2025)
In the context of digital transformation in education, traditional pedagogical models centered on content delivery are increasingly being questioned. The focus is shifting towards models that prioritize knowledge construction, where students engage actively with the content to build deeper understanding. This article examines how digital pedagogical models can evolve from a teacher-centered approach to a learner-centered one, fostering an environment where learners co-create knowledge. It discusses the challenges and opportunities that come with this shift and proposes a conceptual framework for digital pedagogical practices that align with constructivist principles. Through analysis of existing literature, this paper highlights the key factors influencing effective digital pedagogy, including technology integration, learner engagement, and the role of educators in facilitating active learning. The results and discussion section also incorporates practical examples, presenting tables with detailed comparisons of different digital pedagogical strategies, illustrating their benefits and limitations.